The focus particles net ‘even’, tiktai ‘only’, gi and juk in the 16th–17th century Lithuanian writings - Jasionytė-Mikučionienė, Erika (Baltistica, 2020)
The paper investigates the functions and usage of the focus particles net ‘even’, tiktai ‘only’ gi and juk in the selected Old Lithuanian texts from the 16th–17th centuries. The aim is to find out how widely the focus meaning is evidenced in the analysed writings, whether there are traces of further semantic development from the focus to discourse meanings. Special attention is paid to the scope (or focus) of the particles: an attempt is made at discovering whether the phrases (and of what structural type) or the whole proposition of the sentence falls within the scope of the particles. Three old texts were chosen for analysis: Jonas Bretkūnas’ Postilla (1591), Mikalojus Daukša’s Postilla (1599), Konstantinas Sirvydas’ Punktai sakymų (1629–1644). The analysis revealed that the focus meaning of the particles net, tiktai and gi was quite well-attested. Gi and tiktai have a widely developed focus meaning, while net has a less developed meaning under consideration. The particle juk is exclusively associated with the discourse function of common ground or uncontroversial information, which is witnessed typologically – in the Circum-Baltic languages. The latter function is fulfilled by the particle gi as well.